2011
DOI: 10.1074/jbc.m110.197707
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Bcl-2-interacting Mediator of Cell Death (Bim) E3 Ligase, Tripartite Motif-containing Protein 2 (TRIM2), and Its Role in Rapid Ischemic Tolerance-induced Neuroprotection

Abstract: We have previously shown that the cell death-promoting protein Bcl-2-interacting mediator of cell death (Bim) is ubiquitinated and degraded following a neuroprotection-conferring episode of brief ischemia (preconditioning). Here, we identify the E3 ligase that ubiquitinates Bim in this model, using a proteomics approach. Using phosphorylated GST-Bim as bait, we precipitated and identified by mass spectrometry tripartite motif protein 2 (TRIM2), a RING (really interesting new gene) domain-containing protein. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 31 publications
1
48
1
Order By: Relevance
“…TRIM2 is a member of the TRIM superfamily mainly expressed in the brain [18,44] containing a RING finger, B-box, and coiled-coil domains in the amino terminus. TRIM2 interacts with NF-L and regulates its metabolism by ubiquitination [8].…”
Section: Discussionmentioning
confidence: 99%
“…TRIM2 is a member of the TRIM superfamily mainly expressed in the brain [18,44] containing a RING finger, B-box, and coiled-coil domains in the amino terminus. TRIM2 interacts with NF-L and regulates its metabolism by ubiquitination [8].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some members of the TRIM family of ubiquitin ligases have been shown to be involved in the regulation of these signaling pathways [23,28,31,32]. Thus, it is important to clarify the correlation between the functions of TRIM family ubiquitin ligases and the effects of these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A transgenic mouse study demonstrated that replacement of the ERK phosphorylation sites with Ala prolongs BIM protein half-life and increases apoptotic cell death in response to serum starvation [4]. SCF β-TrCP , c-CBL, and TRIM2 are the E3 ligases responsible for ERK-dependent BIM degradation [100102]. Notably, SCF β-TrCP -mediated BIM ubiquitination requires phosphorylation of the degron sequence containing S93/S94/S98 by RSK (ribosomal S6 kinase), which is promoted by ERK phosphorylation at S69 [101] (Table 1).…”
Section: Post-translational Regulationmentioning
confidence: 99%